2018
DOI: 10.1088/1361-6579/aae0eb
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-based fall detection using a hybrid of tri-axial accelerometer and gyroscope

Abstract: Using multiple inertial parameters improves the specificity of fall detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…This review also found that automatic tracking by wearable devices is another common strategy to promote physical activity in older people. Falling and being at risk of falling can in fact be feasibly and accurately detected by wearable devices (e.g., accelerometers and gyroscopes) [76]. Early studies had already shown that fall detectors reduce a person's fear of falling [77].…”
Section: Discussionmentioning
confidence: 99%
“…This review also found that automatic tracking by wearable devices is another common strategy to promote physical activity in older people. Falling and being at risk of falling can in fact be feasibly and accurately detected by wearable devices (e.g., accelerometers and gyroscopes) [76]. Early studies had already shown that fall detectors reduce a person's fear of falling [77].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, in [33], present a fall classification methodology based on two new inertial parameters: acceleration cubic-product-root magnitude (ACM) and angular velocity cubic-product-root magnitude (AVCM). These indexes have been introduced to improve the selectivity of threshold-based fall detection methods, and evaluate strategies to distinguish falls from other activities of daily life (ADLs).…”
Section: Customized Systemsmentioning
confidence: 99%
“…As alternatives, accelerometers combined with surface electromyography sensors [26], gyroscopes [22], [23], or various bio-signal sensors, including those used to record electrical activity of the heart, blood pressure, pulse oximetry, respiration rate, and body surface temperature [27]. Among these various options, we have chosen a heart rate sensor because higher accuracy levels have been achieved to an extent using a multi-dimensional combination of physiological and kinematic parameters [15].…”
Section: Introductionmentioning
confidence: 99%